Bi-based mono-core superconductor tapes : fabrication process and the effect of the thermomechanical treatment on the transport properties / K.T. Lau and R-Abd Shukor - Lau, K.T.; R-, Abd Shukor (Faculty of Applied Sciences, 2005)
Fabrication of the Bi-based tapes started with the preparation of its precursor powder with composition of Bi1.8 Pb 0.4 Sr2 Ca2.2 Cu3 O10+y. The post-annealed powder with a majority of 2212 phase was then ground before it was packed into a silver tube. Then the composite was sway-rolled and drawn into wire with diameter of 1.08 mm. To make it into tape form, the wire was cut into shorter length before went through rolling process using a roller machine. The tapes were divided into sample groups and underwent different thermo-mechanical treatments. All the final processed Bi-based tapes had mixed superconductor phases of 2223 and 2212. Most part of HTSC grains in the tapes melted during the sintering. Transport voltage-current characteristics of the tapes was found to obey the power law relationship. The thermo-mechanical treatment was found necessary to improve the structural quality of the tapes.